The Influence Of The Work Environment On Employee Performance At The Tourism, Culture, Youth And Sports Office Dairi Regency - Jumali; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2024)
The purpose of this study is to find out and analyze the influence of the Work Environment on Employee Performance at the Dairi Regency Tourism, Culture, Youth and Sports Office. This research was carried out at the Dairi Regency Tourism, Culture, Youth and Sports Office. The type of research is quantitative associative. The sample in this study is 96 employees with ASN and honorary status at the Dairi Regency Tourism, Culture, Youth and Sports Office. The sampling technique in this study used the entire population of 96 people. The results of the study show that the Work Environment has a significant influence on Employee performance as shown by the T-Statistic value of 5.078 > 1.660 and the P Value of 0.000 < 0.05. This shows that improvements in the Work Environment can improve the performance of Employees at the Dairi Regency Tourism, Culture, Youth and Sports Office.